Preparation and Surface Modification of ZnO/Al2O3 Nanocomposites - Dong, Wenjie; Ma, Shiyu; Wang, Xuegang; Cao, Junlei (Asian Journal of Chemistry, 2012)
In this work, the ZnO/Al2O3 nanocomposites are prepared by situ-modified method and the ZnO/Al2O3 nanocomposites are modified by silane coupling agent. By using the particle size analysis, it is confirmed that the mean particle size of modified ZnO/Al2O3 nanocomposites is 68 nm and its distribution is uniform. The dispersion of modified ZnO/Al2O3 nanocomposites is analyzed by the absolute value of ZnO/Al2O3 nanocomposites zeta potential. Through scanning electron microscope studies, it is found that the silane coupling agent improve the dispersibility of ZnO/Al2O3 nanocomposites. The hydroxyl groups on the surface of ZnO/Al2O3 nanocomposites can interact with hydroxyl groups of silane coupling agent and an organic coating layer is formed. The formed covalent bands are testified by Fourier transform infrared spectra (FT-IR). The dispersion stabilization of modified ZnO/Al2O3 nanocomposites is significantly improved due to the introduction of grafted polymers on the surface of nanoparticles. In addition, their surfaces become organic phase from inorganic phase.